2008
DOI: 10.1007/978-3-540-85565-1_104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Prototype of the Mimamori-care System for Persons with Dementia

Abstract: Abstract. We aim to clarify the requirements for the mimamori-care system in the group home to support caregivers who take care of persons with dementia (PWD). We investigated the effects of the prototype, which consists of several cameras and monitors, by interviewing eleven caregivers. We found that the prototype system not only helps the caregivers to watch out the people with dementia but also removes some stress caused by taking excessive precaution to residents' behaviors. Caregivers however reported som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…The series of interviews revealed that the system reduced caregivers' physical and mental stress, as previously reported (Sugihara et al 2008;Sugihara and Fujinami 2011), comparing the situation before and after system deployment. Caregivers reported that some areas became blind spots at night because fewer caregivers were available to work overnight.…”
Section: Alleviating Stressmentioning
confidence: 70%
See 1 more Smart Citation
“…The series of interviews revealed that the system reduced caregivers' physical and mental stress, as previously reported (Sugihara et al 2008;Sugihara and Fujinami 2011), comparing the situation before and after system deployment. Caregivers reported that some areas became blind spots at night because fewer caregivers were available to work overnight.…”
Section: Alleviating Stressmentioning
confidence: 70%
“…The wall and door removal in GH-D can be considered in this case, especially in terms of its spatial layout. Our previous study showed that caregivers may lock doors that directly leading to the outside if caregivers and managers do not have the skills and leeway to maneuver dementia-related issues such as aimless wandering (Sugihara et al 2008;Sugihara and Fujinami 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the overall acceptance of video-based AAL, the results from the selected 22 studies show that acceptance attitudes toward video-based AAL technologies are rather conditional. Few studies reported more concerns over the use of monitoring systems than advantages [ 33 , 49 ]; however, most of the studies note that depending on diverse variables, the acceptance of video-based AAL technologies also vary. Generally, positive attitudes toward technology were related to greater acceptance of sharing and recording health-related information.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies mainly identified possible negative effects on formal caregivers, such as feeling threatened by being under constant surveillance [ 33 , 36 , 49 ]. These studies also highlighted the violation of the privacy rights of caregivers.…”
Section: Resultsmentioning
confidence: 99%
“…Most existing smart systems target internet-based reminiscent therapy for seniors and telecommunication between the patient and the physician [5]. Some systems are dedicated to help PCE at work or at home by memorizing and delivering necessary data [6]- [7].The others aim to assist old people at group homes and hospitals [8]- [11] A good survey of assistive technologies and systems can be found in [12].…”
Section: Introductionmentioning
confidence: 99%